The legal and historical process of constitutional construction of Spain. Notes on the role of the High Inspection in the educational cohesion of the Autonomous State - Foces Gil, Jaime Antonio (Avances en Supervisión Educativa, 2022)
The Kingdom of Spain is based on the existence of a constitutional pact that has a first derivative in the territorial structure of the nation: the autonomous State. We analyze how and why it emerged in 1979 and explain what it owes its current configuration to. The Autonomous State begins its journey before the Constitution itself, with the echoes of the territorial organization of the Second Republic and evolves in an unscheduled way until the Autonomous Communities are generalized. Today it shows a homogeneous structure more similar to a federation than to a simply decentralized State. We briefly reflect on the importance of High Education Inspection as constitutional mechanism of State cohesion. We conclude the analysis pointing out the need for the State to be articulated and integrated for the good of the citizens and we warn about the rebirth of concepts surpassed by history such as those of nation and nationalism.
Keywords: Educational administration; Constitution; Autonomous State; nationalism; autonomy; decentralization; Autonomous Communities; High Inspection